SARM regulates CCL5 production in macrophages by promoting the recruitment of transcription factors and RNA polymerase II to the Ccl5 promoter - BOWIE, ANDREW (My University, 2014)
The four Toll/IL-1R domain-containing adaptor proteins MyD88, MAL, TRIF, and TRAM are well established as essential mediators of TLR signaling and gene induction following microbial detection. In contrast, the function of the fifth, most evolutionarily conserved Toll/IL-1R adaptor, sterile α and HEAT/Armadillo motif-containing protein (SARM), has remained more elusive. Recent studies of Sarm(-/-) mice have highlighted a role for SARM in stress-induced neuronal cell death and immune responses in the CNS. However, whether SARM has a role in immune responses in peripheral myeloid immune cells is less clear. Thus, we characterized TLR-induced cytokine responses in SARM-deficient murine macrophages and discovered a requirement for SARM in CCL5 production, whereas gene induction of TNF, IL-1β, CCL2, and CXCL10 were SARM-independent. SARM was not required for TLR-induced activation of MAPKs or of transcription factors implicated in CCL5 induction, namely NF-κB and IFN regulatory factors, nor for Ccl5 mRNA stability or splicing. However, SARM was critical for the recruitment of transcription factors and of RNA polymerase II to the Ccl5 promoter. Strikingly, the requirement of SARM for CCL5 induction was not restricted to TLR pathways, as it was also apparent in cytosolic RNA and DNA responses. Thus, this study identifies a new role for SARM in CCL5 expression in macrophages.
PUBLISHED
Keywords: Toll-like receptors; Immunology, Inflammation & Infection; Immune System; Immunology, Immunotherapy; Inflammation; Molecular Biology; SIGNAL-TRANSDUCTION PATHWAYS